Retrospective evaluation of planning margins for patients undergoing radical radiation therapy treatment for bladder cancer using volumetric modulated arc therapy and cone beam computed tomography. Issue 4 (20th July 2021) - Dower, Kathleene; Ford, Andriana; Sandford, Michael; Doherty, Andrew; Greenham, Stuart; Kerin, Luke; Dwyer, Patrick; Hansen, Carmen; Westhuyzen, Justin; Shakespeare, Thomas
Abstract: Introduction: Current contouring guidelines for curative radiation therapy for muscle‐invasive bladder cancer (MIBC) recommend margins of 1.5–2.0 cm, applied to the clinical target volume (CTV). This study assessed whether the use of volumetric modulated arc therapy (VMAT), cone beam computed tomography (CBCT) and strict bladder preparation allowed for a reduced planning target volume (PTV) expansion, resulting in lower doses to surrounding organs at risk (OARs). Methods: Daily CBCT images for 12 patients (382 scans total) were retrospectively reviewed against four potential PTV margins created on and exported with the reference CT scan. To form the PTVs, three isotropic expansions of 0.5, 1.0 and 1.5 cm were applied to the CTV, as well as an anisotropic expansion of 1.5 cm superiorly and 1.0 cm in all other dimensions. Following treatment completion, the CBCTs were visually assessed to determine the margins encapsulating the bladder. For retrospective planning purposes, the 1.0‐cm and anisotropic margins were compared with the previously recommended margins to determine differences in OAR doses. Results: The 0.5‐, 1.0‐ and 1.5‐cm isotropic margins (IM) and the anisotropic margin (ANIM) covered the CTV in 46.1, 96.8, 100 and 100% of CBCTs retrospectively. Doses to OARs were significantly lower for the reduced margin plans for the small bowel, rectum and sigmoid. Conclusion: Bladder planning target volumes may be safely reduced. We endorse a PTV margin of 1.0cm anteriorly, posteriorly and inferiorly with 1.0–1.5 cm superiorly for radical whole bladder cases using strict bladder preparation, VMAT and pretreatment CBCTs. Abstract : This study assessed whether the use of volumetric modulated arc therapy (VMAT), cone beam computed tomography (CBCT) and strict bladder preparation allowed for a reduced planning target volume (PTV) expansion, resulting in lower doses to surrounding organs at risk (OARs). The study showed we could reduce the PTV margin to 1.0 cm anteriorly, posteriorly and inferiorly with 1.0–1.5 cm superiorly for radical whole bladder cases using strict bladder preparation, VMAT and pre‐treatment CBCTs. A reduction in margin resulted in significantly lower OAR doses.